A CFD presentation and visualization for a new model that uses interceptors to harness hydro-energy at the wash of fast boats. (15th January 2017) - Talaat, Waleed M.; Hafez, K.A.; Banawan, A.A.
Abstract: This paper proposes a scheme for harnessing flow energy downstream of the propeller of boat, using a perforated interceptor plate. The proposed scheme is the first of its kind, which is thought to provide electrical energy if applied on board fast boats. Mainly, we study a model composed of an elbow piping set that is connected to a perforated interceptor plate, constituting the inlet configuration (or the penstock) to water turbine. A commercial CFD tool was essentially implemented to predict the model's initial gain and to present some of the important fluid dynamics aspects of the problem. We studied the flow upstream of the proposed model of interceptor and illustrated the effects of the upstream external flow and the boundary layer on the flow through the piping bends and downstream. As expected, the traditional interceptor model is majorly affected by the modelled perforations. Hence, the performance of the perforated interceptors was investigated. A remarkable flow structure in the developing and fully developed regions of the model was depicted. Finally, we reached at some conclusions about the impact on ship performance and the possible measures that may increase the energy gain in the future. Highlights: A new penstock model incorporating a perforated interceptor was proposed. A new secondary flow structure in 90-degree bend of the penstock was reported. In very high speeds, the penstock with many pipes reduced the bare hull resistance. The proposed penstock dose not actually affect interceptors in very high speeds.